The Synergistic Antiwear Performances of Organic Titanium Compounds Containing Sulfur with Borate Ester Additive - Xu, Xin; Hu, Jian-Qiang; Xie, Feng; Guo, Li; Ma, Jun; Yang, Shi-Zhao (Journal of Spectroscopy, 2018)
Two oil-soluble organic titanium compounds (OTCs) such as titanium dialkyldithiocarbamate (TiDDC) and sulfurized titanate (TiS) were synthesized and identified by Fourier-transform infrared spectroscopy (FTIR). The antiwear and extreme pressure properties of TiDDC or TiS with borate ester containing nitrogen (BNO) additive in mineral base oils were evaluated by four ball tester. The results show that TiDDC and TiS not only possess good antiwear and load-carrying properties, respectively, but also exhibit good antiwear synergism with BNO additive without impairing extreme pressure performances. Moreover, the synergistic antiwear properties of the said additives are improved significantly under the optimum additives ratios. The topography of wear scar and the composition and chemical states of typical elements on the rubbing surfaces were analyzed by scanning electron microscopy (SEM) with energy dispersive X-ray (EDX) and X-ray photoelectron spectrometer (XPS). The proposed synergistic antiwear mechanism involves an effective interaction between TiDDC or TiS and BNO additive, respectively.